Enhanced pain sensitivity in obese patients with obstructive sleep apnoea syndrome is partially reverted by treatment: An exploratory study. (16th February 2023) - Lahaye, Clément; Miolanne, Magalie; Farigon, Nicolas; Pereira, Bruno; Dubray, Claude; Beudin, Patricia; Greil, Annick; Boirie, Yves
Abstract: Background: Obesity is frequently associated with obstructive sleep apnoea syndrome (OSA) and chronic pain. OSA as well as continuous positive airway pressure (CPAP) treatment may modulate the pain perception threshold (PT) in patients with obesity. Methods: In this prospective, longitudinal study, all patients admitted for obesity assessment were screened for OSA by nocturnal polygraphy (SOMNOcheck ®, IAH ≥10) and performed mechanical (Von Frey electronic device) and electrical (PainMatcher ® ) pain tests. Those with severe OSA were retested for PT 1 month after initiation of CPAP therapy. Newly diagnosed patients with severe OSA (hypopnea apnoea index >30) have been offered to start CPAP treatment. Results: Among 85 patients, there were 27 OSA patients, aged between 40 ± 13.2 years with a BMI of 42 ± 7.2 kg/m 2 . Severe OSA patients ( N = 11) showed a lower PT than non‐OSA patients ( N = 58) during mechanical (177 ± 120 vs. 328 ± 136 g, p < 0.01) and electrical methods (7.4 ± 6.4 vs. 12.9 ± 6.7 stimulation duration steps; p = 0.03). In the severe OSA group ( N = 7), an increased PT was observed 1 month after CPAP treatment during mechanical pain testing (298 ± 69 vs. 259 ± 68 g, p < 0.05), but not during electrical pain testing (11.5 ± 3.0 vs. 12.4 ± 3.8 stimulation duration steps, p = 0.50). Conclusion: In patients with obesity, this exploratory study showed that the presence of an OSA is associated with a decreased PT, whereas implantation of a CPAP device tends to normalize pain perception.